The Evolution of Polymorphic Hybrid Incompatibilities in House Mice. Issue 3 (24th April 2018) - Larson, Erica L; Vanderpool, Dan; Sarver, Brice A J; Callahan, Colin; Keeble, Sara; Provencio, Lorraine L; Kessler, Michael D; Stewart, Vanessa; Nordquist, Erin; Dean, Matthew D; Good, Jeffrey M
Abstract: Reproductive barriers are often assumed to arise from fixed genetic differences between species, despite frequent individual variation in the strength of reproductive isolation between populations. Larson et al. report polymorphism... Resolving the mechanistic and genetic bases of reproductive barriers between species is essential to understanding the evolutionary forces that shape speciation. Intrinsic hybrid incompatibilities are often treated as fixed between species, yet there can be considerable variation in the strength of reproductive isolation between populations. The extent and causes of this variation remain poorly understood in most systems. We investigated the genetic basis of variable hybrid male sterility (HMS) between two recently diverged subspecies of house mice, Mus musculus domesticus and Mus musculus musculus . We found that polymorphic HMS has a surprisingly complex genetic basis, with contributions from at least five autosomal loci segregating between two closely related wild-derived strains of M. m. musculus . One of the HMS-linked regions on chromosome 4 also showed extensive introgression among inbred laboratory strains and transmission ratio distortion (TRD) in hybrid crosses. Using additional crosses and whole genome sequencing of sperm pools, we showed that TRD was limited to hybrid crosses and was not due to differences in sperm motility between M. m. musculus strains. Based on these results, we argue that TRD likely reflects additional incompatibilities that reduce hybrid embryonic viability. In some common inbred strains of mice, selection against deleterious interactions appears to have unexpectedly driven introgression at loci involved in epistatic hybrid incompatibilities. The highly variable genetic basis to F1 hybrid incompatibilities between closely related mouse lineages argues that a thorough dissection of reproductive isolation will require much more extensive sampling of natural variation than has been commonly utilized in mice and other model systems.